Ways to tackle rural poverty - Akatova, D. S. (ТДАТУ, 2020)
Poverty is a complex and multifaceted problem with both national and international origins. There is no one-size-fits-all solution to this problem that can be applied globally. Rather, countryspecific poverty alleviation programs and international efforts to support national action and the parallel process of creating an international environment conducive to its solution are critical to its solution. Eradicating poverty and hunger, achieving a more equitable distribution of income and developing human resources are still major challenges everywhere. All countries have a shared responsibility to take action to combat poverty.
Keywords: poverty; poverty alleviation; distribution of income